The Transformative Practice of Writing and Teaching Writing - Robbie Clifton Pinter (Journal of the Assembly for Expanded Perspectives on Learning, 2017)
A deep reading of Wendell Berry’s Timbered Choir frames a paean to writing and teaching, despite the challenges of academic life.